The effect of lycopene on the total cytochrome P450, CYP1A2 and CYP2E1 (Medical Journal of Indonesia, 2009)
Aim Some carotenoids such as canthaxantin, astaxanthin and beta apo-8'-carotenal were reported to have modulatory effect on the cytochrome P450. The present study was conducted to investigate the effects of lycopene, a nonprovitamin A carotenoid, on microsomal cytochrome P450, CYP1A2 and CYP2E1. Methods Total cytochrome P450 levels, CYP1A2 and CYP2E1-catalyzed reactions (acetanilide 4-hydroxylation and p-nitrophenol hydroxylation) were studied in the liver microsomes of male Sprague Dawley rats. Microsomes were prepared using differential centrifugation combined with calcium aggregation method. Lycopene was orally administered in the dosages of 0, 25, 50 or 100 mg/kgBW/day for 14 days in a repeated fashion. Data were analyzed using ANOVA test. Results Total cytochrome P450 level and acetanilide 4-hydroxylase activity were unaffected by any of the treatments. The CYP2E1 probe enzyme (p-nitrophenol hydroxylase) was significantly reduced by repeated administration of 100mg/ kgBW/day lycopene (7.88 + 2.04 vs 12.26 + 2.77 n mol/min/mg prot). Conclusion The present results suggest that lycopene does not affect the total cytochrome P450 or CYP1A2 activity but it inhibits the activity of CYP2E1 (p-nitrophenol hydroxylase) in the rat. (Med J Indones 2009; 18: 233-8)